2022
DOI: 10.1101/2022.07.07.497559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myoscaffolds reveal laminin scarring is detrimental for stem cell function while sarcospan induces compensatory fibrosis

Abstract: We developed an on-slide decellularization approach to generate acellular extracellular matrix (ECM) scaffolds that can be repopulated with various cell types to interrogate cell-ECM interactions. Using this platform, we investigated whether fibrotic ECM scarring affected human skeletal muscle progenitor cell (SMPC) functions that are essential for myoregeneration. SMPCs exhibited robust adhesion, motility, and differentiation on healthy muscle-derived myoscaffolds. All SPMC interactions with fibrotic myosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…Thus, while Hh is sufficient to induce fibrosis, it is not necessary. As fibrotic scar tissue is a potent anti-myogenic signal 11,72,73 , this increased fibrosis could also contribute to the myogenic defects we observe after ectopic Hh activation. We also determined whether Hh de-repression could result in fibrosis.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, while Hh is sufficient to induce fibrosis, it is not necessary. As fibrotic scar tissue is a potent anti-myogenic signal 11,72,73 , this increased fibrosis could also contribute to the myogenic defects we observe after ectopic Hh activation. We also determined whether Hh de-repression could result in fibrosis.…”
Section: Discussionmentioning
confidence: 89%
“…POSTN and DCN are known inhibitors of myoblast migration and differentiation. Stearns-Reider et al demonstrated that skeletal muscle progenitor cells seeded into heavily fibrotic areas of mdx dECM scaffolds had reduced migratory capacity, a rounded morphology, and reduced differentiation potential compared to mildly-fibrotic areas of mdx and WT matrices (Stearns-Reider et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Slides were stored at -80°C. Decellularization was performed as in Stearns-Reider et al,2022 with the following modifications (Stearns-Reider et al, 2022). Slides were allowed to thaw to room temperature for 1 hr prior to decellularization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometry dataset was first published in part in Stearns-Reider et al (47). Quadriceps muscles were harvested from 20-week-old male wild-type, mdx , and mdx TG (line 3) mice and snap frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%